The role of corporate archives in the era of blockchain and AI - Pier Paolo Peruccio; Martina Liboni; Francesca Mucchetti (Agathón, 2025)
In the context of the digital transition, this contribution analyses the increasingly central role of corporate archives as custodians of collective memory. In this scenario, the application of AI proves to be a promising tool for facilitating the analysis and automatic indexing of documents, overcoming traditional physical barriers and making archival holdings easier to consult; at the same time, blockchain technology offers guarantees regarding source integrity and authenticity. Through the examination of three case studies, the collaboration between Museimpresa and Google Arts & Culture and the experiences of Italgas and Riva, the article aims to assess how these technologies are transforming the way corporate archives are accessed and used, opening new perspectives for education, research, and innovation, in line with Sustainable Development Goal no. 4 of the 2030 Agenda. The article also highlights the need for an ethical approach to using AI and the environmental impact generated by blockchain. The contribution is addressed to companies, researchers, and designers to promote a more conscious use of digital technologies applied to archival heritage.